Mega-sports event participation and social capital : mediating effect of the social legacy recognition of 2018 PyeongChang Winter Olympics - Kim, Subin (2019)
Researchers who have studied mega-sporting events argue that such events have been purely in the interests of the global and corporate elite, leaving little social impact in the community at large, and they have insisted that such events should pay more attention to creating long-term values for the community. Therefore, the purpose of this study is to establish a research model encompassing participation, social capital, and social legacy of mega- sporting events, and to identify the role that sport event participation plays in developing social capital in host regions’ community through the case study of the 2018 PyeongChang Olympic games. A total of 213 structured surveys were administered to local residents in two cities: Gangneung and PyeongChang, where the games were held. The data was statically analyzed by using factor analysis, correlation analysis, ANOVA, and multiple regression analysis in SPSS 19.0. The analysis results for the research model are as follows. First, multiple regression analyses were conducted to verify the impact of participation timing, participation type and motivation on trust, network, community participation and reciprocal norms, which are sub-components of participation level. the most influential variable on trust and the network was found to be the period of participation, then the participation types, and finally the motivations. The reciprocity norm was found to be significantly influenced by the period of participation and type, in order but participation motivation showed no influence. Second, mediation analysis showed that the period of the participation displayed a partial mediated effect on the trust, the network, and the reciprocity norm, which are the elements of social capital mediated by social legacy recognition. Third, the types of the participation showed a partial mediated effect on the trust, the network, and the reciprocity norm mediated by the social legacy recognition. Last, the motivation of the participation showed a partial mediated effect on the trust, the network mediated by the social legacy recognition, but not with the reciprocity. Because the research has been carried out within a particular context, there are limitations when generalizing and explaining the relationship between the development of social capital and mega- sports events taking place in other regions. For more concrete theoretical development, longitudinal studies such as before-and-after comparisons are needed to track long-lasting impact, because social capital can be developed and transformed over time. However, the findings of this study can be used as valuable information for future sports mega-sports event organizing/ governing bodies.